PERANAN BAWASLU DALAM PENANGANAN PELANGGARAN PEMILU TAHUN 2019 DI KOTA SERANG BERDASARKAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 - Irwan, Devi; Asnawi, Asnawi; Pramono, Aris Setyanto; Maulana, Ayang Fristia (LPPM Universitas Bina Bangsa, 2023)
Supervision of the implementation of elections in the city of Serang carried out by Bawaslu of Serang city is regulated in Article 101, Article 103 and Article 104 of Law Number 7 of 2017 concerning General Elections, in order to achieve direct, public, free, secret, honest and fair and quality elections in the city of Serang. In the 2019 elections, Bawaslu of Serang city recorded 10 election violations that occurred. Of the 10 violations, 6 violations were based on findings on the ground and 4 violations were based on reports of alleged election violations. Bawaslu of Serang city divides four types of violations in elections, namely: Violations of Election Administration, Violations of the Code of Ethics for Election Organizers, Election Crimes; and other Violations of The Law. This research uses an empirical juridical research approach. Empirical legal research or in other words is referred to as sociological legal research or field research, which is dotted with primary / basic data, namely data obtained directly from the first source through field research, which is carried out through interviews, observations (observations), or the dissemination of questionnaires. The role of Bawaslu of Serang city in dealing with election violations is in the form of receiving and following up on reports related to alleged election violations, examining and reviewing election violations and recommending the results of examinations and their assessments to relevant agencies, mediating or adjudicating, and resolving disputes in the electoral process,recommend to the relevant agencies regarding the results of supervision of the neutrality of all parties in the conduct of elections, request the necessary information materials to relevant parties in order to prevent and crack down on election violations and disputes over the electoral process and establish a sub-district panwaslu and appoint and dismiss members of the sub- district panwaslu, as well as exercise other powers in accordance with the provisions of the laws and regulations